An assessment of initiatives to combat the brain drain in Ghana - Amponsah, Yaa Obenewa (My University, 2016)
Today, it is estimated that annually, 70,000 skilled Africans depart their nations of origin to pursue professional and educational opportunities abroad. Many leaders, policymakers and developmental practitioners believe that this steady stream of emigrants—commonly referred to as brain drain—has a substantial impact on the ability of African nations to develop. As such, brain drain is rapidly becoming one of the most salient issues on the African development agenda. Conventional wisdom had it that once nations improved their political, economic and social conditions, brain drain would abate. Yet, some countries, which have succeededin advancing socio-economic reforms and political freedoms, are seeing an increase in skilled emigration. The West African nation of Ghana is one nation that is experiencing this problem, to the detriment of key areas such as education and healthcare. In an effort to curtail the impact of brain drain on development, several entities have undertaken initiatives to mitigate the effects of the phenomenon.This research will assess efforts to ameliorate the effects of brain drain in Ghana. Specifically, it examinestwo programs facilitated by the International Organization for Migration—the Return of Qualified African Nationals initiative and Migration for Development in Africa—as well as interventions by the Republic of Ghana. The purpose of the study is to better understand the objectives of these brain gain initiatives, how the programs are facilitated and their impact in order to extrapolate lessons that can assist future actors in formulating more effective measures to combat brain drain.
Thesis (M.A.(International Relations))--University of the Witwatersrand, Faculty of Humanities, 2016.
Keywords: Brain drain--Ghana; African diaspora; Ghana--Emigration and immigration